(untitled) (Eurasian Research Bulletin, 2025)
The article discusses the use of neuroexercises as an effective means of developing cognitive abilities in children of primary school age. The relevance of the topic is due to increased demands on the cognitive development of modern schoolchildren and the search for new teaching methods. The results of a number of modern studies show that the systematic use of neuroexercises leads to a significant improvement in memory, attention, academic performance and executive functions in primary school children. Neuroexercises are a promising tool in neuropedagogy , contributing to the formation of strong neural connections and the harmonious development of the cognitive sphere of children.